ISOMORPHISM OF PREDICATE MODEL COMPARATOR IDENTIFICATION - Suprun, T. S.; Shabanov-Kushnarenko, S. Yu. (Radio Electronics, Computer Science, Control, 2008)
The different models of comparison identification are considered which use predicates of equivalence and difunctionaliance. The theorems of isomorphism of offered models are proved.